2014
DOI: 10.1186/1756-0500-7-897
|View full text |Cite
|
Sign up to set email alerts
|

The cross-cultural process of adapting observational tools for pediatric pain assessment: the case of the Dental Discomfort Questionnaire

Abstract: BackgroundA rigorous cross-cultural adaptation process of an existing instrument could be the best option for measuring health in different cultures, instead of developing a new tool, and prior to psychometric and validation testing. The Dental Discomfort Questionnaire (DDQ), a validated instrument for assessing toothache in young children, has not been cross-culturally adapted so far. This study aimed to explore the detailed phases of the cross-cultural adaptation process of a pain assessment tool, presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…All studies [ 17 35 ] have a cross-sectional design and were carried out in Brazil. The mean age of participants ranged from 2 [ 20 ] to 15.42 years [ 22 ], however, two studies did not report this information [ 21 , 32 ]. The number of participants ranged from 20 [ 32 , 35 ] to 342 [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies [ 17 35 ] have a cross-sectional design and were carried out in Brazil. The mean age of participants ranged from 2 [ 20 ] to 15.42 years [ 22 ], however, two studies did not report this information [ 21 , 32 ]. The number of participants ranged from 20 [ 32 , 35 ] to 342 [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“… SANTOS et al,2016 [ 28 ] Brazil Cross-sectional 90 boys and 104 girls, 13 years old NR Absent Present Adolescents Discriminant validity revealed a significant difference between the mean scores for the domains of dental self-confidence and psychological impact between groups with and without malocclusion. The Brazilian version of the PIDAQ for adolescents has satisfactory psychometric properties and applies to this age group in Brazil DAHER et al,2014 [ 21 ] Brazil Cross-sectional study 30 parents/ guardians of children, age N.R. English Present Present Children Conceptual and item analyses showed that there are similarities in the DDQ construct between the original and Brazilian cultures that require small modifications.…”
Section: Resultsmentioning
confidence: 99%
“…The developer of the PCS-P authorized its translation and cross-cultural adaptation to Brazilian Portuguese, and it was carried out in accordance with previously published guidelines 16 17 , 18 Two bilingual translators (T1 and T2), whose native language is Brazilian Portuguese, translated the PCS-P separately and produced two independent written translations. T1 was aware of the concepts that were being examined in the questionnaire in order to provide equivalence from a clinical perspective.…”
Section: Methodsmentioning
confidence: 99%
“…In the reception area of the dental offices, one of the two trained researchers individually interviewed each parent/other relative using the Brazilian-Portuguese PCS-P and the Brazilian Dental Discomfort Questionnaire(DDQ-B) 18 19 The DDQ-B was used as an observational measure of the child’s dental pain, analyzing the concurrent and construct validity properties of the PCS-P, given that we intended to check whether PCS-P was able to be used in assessments of patients with dental pain/discomfort.…”
Section: Methodsmentioning
confidence: 99%
“…Campo Magro has a population of 24,843 residents and a Human Development Index of 0.701, which is slightly below the Brazilian average (0.755). Its economy is based primarily on family farming and tourism activities [20].…”
Section: Eligibility Criteria and Characteristics Of Samplementioning
confidence: 99%